2000
DOI: 10.2460/ajvr.2000.61.796
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum leptin immunoreactivity and body fat mass as estimated by use of a novel gas-phase Fourier transform infrared spectroscopy deuterium dilution method in cats

Abstract: Leptin is in the serum of domestic cats in free (> 78%) and apparently bound forms. The relationship between body fat and serum leptin concentration was similar to that observed in humans and rodents and indicative of a lipostatic role for leptin in cats. Cats that have an overabundance of body fat appear to be less sensitive to the weight-normalizing action of leptin than cats of ideal body condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 30 publications
11
87
1
Order By: Relevance
“…In addition, we confirmed that anti-canine leptin antibody showed differences in immunoreactivity among other species as compared to the canine leptin [14]. Recently, Backus et al [1] reported serum leptin-like immunoreactiv-ity in cats was poorly measurable with a RIA based on antisera against mouse, rat, human, and primate leptins, suggesting the low immunoreactivity of these antisera to feline leptin. These facts indicate that species-specific leptin and/or anti-leptin antibody is required for better understanding the physiological and pathological functions of leptin in detail.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, we confirmed that anti-canine leptin antibody showed differences in immunoreactivity among other species as compared to the canine leptin [14]. Recently, Backus et al [1] reported serum leptin-like immunoreactiv-ity in cats was poorly measurable with a RIA based on antisera against mouse, rat, human, and primate leptins, suggesting the low immunoreactivity of these antisera to feline leptin. These facts indicate that species-specific leptin and/or anti-leptin antibody is required for better understanding the physiological and pathological functions of leptin in detail.…”
Section: Discussionsupporting
confidence: 63%
“…Leptin concentrations are positively correlated with adipose tissue mass (Appleton et al, 2000;Backus et al, 2000;Belsito et al, 2009). Backus et al (2000) used linear regression and estimated that for every 1 g increase in BW, a 1.2 ng/ml increase in leptin occurred.…”
Section: High-protein Diet Following Ovariohysterectomymentioning
confidence: 99%
“…Backus et al (2000) used linear regression and estimated that for every 1 g increase in BW, a 1.2 ng/ml increase in leptin occurred. In the current study, circulating blood leptin concentrations not only increased over time in cats fed both diets, but were also greater in MP-fed cats.…”
Section: High-protein Diet Following Ovariohysterectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma concentrations of leptin are positively correlated with body fat content in various mammalian species including ruminants [3][4][5][6][7][8][9][10][11]. Therefore, circulating leptin is a suitable marker for adiposity in livestock animals and pets, and for assessment of long-term nutritional condition in wild animals.…”
Section: Introductionmentioning
confidence: 99%